Research on investment risk influence factors of prefabricated building projects - Li, Xiao-Juan (Journal of Civil Engineering and Management, 2020)
Prefabricated construction is an effective and efficient approach to improve construction processes, productivity, quality, and cost-effectiveness. There are, however, practical problems in this approach, including higher risk levels, and cost and time overruns. This study aims to develop a systematic approach for determining the key factors that affect investment risk of prefabricated building projects and assess this risk. Based on literature review, a structured questionnaire was distributed to 210 China-based construction organizations. Relevant evaluation index weights were obtained via questionnaire, and the application of structural equation modelling led to quantitative evaluation of investment risk in the prefabricated construction industry. The results show that the following systems have the most influence on investment risk (from high to low): economy, technology, market, management, and policy, and that the investment risk of such projects can be assessed using structural equation modelling. Relevant measures are presented to guide investment risk evaluation of projects. This study contributes to literature by considering investment risk influencing factors in this field. Further, the findings can help in understanding the implementation and investment risk control of prefabricated building projects, while providing valuable information to departments that make decisions on improving investment risk performance of such projects.